Successful treatment of lung adenocarcinoma complicated with a rare compound EGFR mutation L833V/H835L using aumolertinib: a case report and literature review - Li, Linlin; Huang, Siyuan; Qin, Liying; Yan, Ningning; Shen, Shujing; Li, Xingya (Frontiers in Pharmacology, 2023)
The deletion of exon 19 and the Leu858Arg mutation of exon 21 are the most frequently observed mutations in the epidermal growth factor receptor (EGFR) gene, and patients with these mutations have shown significant benefits from EGFR-tyrosine kinase inhibitors (TKIs). However, there exists a small subgroup of patients with uncommon/rare mutations of EGFR, including compound mutations, which display a high degree of heterogeneity in terms of clinical features and variable sensitivities to EGFR-TKIs. The understanding of these uncommon mutations and their response to targeted therapy is still unclear and requires further investigation.We presented a case of a never-smoking patient with lung adenocarcinoma and brain metastasis. Initially, she received chemotherapy plus immune checkpoint inhibitor as first-line therapy as no EGFR mutations were detected by amplification-refractory mutation system-polymerase chain reaction. However, disease progressed rapidly. Subsequently, next-generation sequencing was carried out and revealed a rare compound mutation, L833V/H835L, in exon 21 of EGFR. As a result, she was switched to second-line therapy with the third-generation TKI aumolertinib, which demonstrated good efficacy.The patient was evaluated for a remarkable progression-free survival of 18 months and an overall survival of 29 months. Conclusion: The present study supports that aumolertinib might be a good 3 treatment option for advanced NSCLC patients with EGFR L833V/H835L mutation, particularly in patients with brain metastasis. Furthermore, conducting a comprehensive screening for gene mutations is crucial in effectively identifying potential oncogenic driver mutations and guiding mutation-targeted therapy decisions in clinical practice.